Electronic Commerce in Increase the Competitiveness of the Country's Economy - Makhmudovich, Baymuradov Shokhrukh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
What areas should be developed and what reforms should be implemented to increase the competitiveness of the country's economy. At a time when all countries are on the path of development, issues such as how Uzbekistan can increase its competitiveness and the role of electronic trade in this have been considered.